MEWUJUDKAN KOMUNITAS ADAT TERPENCIL SEJAJAR DENGAN MASYARAKAT PADA UMUMNYA - Sugiyanto, Sugiyanto; Syawie, Mochammad (Sosio Informa, 2007)
Indigenous people is local social culture groups, separately and uninvolved in network and services in social, economic, or politic. The separated that mean social culture, there is gap between level of social culture in tribes with Indonesian conditions enclosed. The means of development are discontinuously to progress for people. â€œProgressâ€ is useful toward humanity aspect from development, and measured with awareness and capability a part of community have to better life and welfare. Keyword : Indigenous people, empowerment, social welfare.